Real‐time observation of the conformational dynamics of mitochondrial Hsp70 by spFRET. (26th April 2013) - Sikor, Martin; Mapa, Koyeli; von Voithenberg, Lena Voith; Mokranjac, Dejana; Lamb, Don C
<x xml:space="preserve">Abstract</x> The numerous functions of the important class of molecular chaperones, heat shock proteins 70 (Hsp70), rely on cycles of intricate conformational changes driven by ATP‐hydrolysis and regulated by cochaperones and substrates. Here, we used Förster resonance energy transfer to study the conformational dynamics of individual molecules of Ssc1, a mitochondrial Hsp70, in real time. The intrinsic dynamics of the substrate‐binding domain of Ssc1 was observed to be uncoupled from the dynamic interactions between substrate‐ and nucleotide‐binding domains. Analysis of the fluctuations in the interdomain separation revealed frequent transitions to a nucleotide‐free state. The nucleotide‐exchange factor Mge1 did not induce ADP release, as expected, but rather facilitated binding of ATP. These results indicate that the conformational cycle of Ssc1 is more elaborate than previously thought and provide insight into how the Hsp70s can perform a wide variety of functions.